2014
DOI: 10.1111/cen.12443
|View full text |Cite
|
Sign up to set email alerts
|

Silent, but not unseen: multimicrocystic aspect on T2‐weighted MRI in silent corticotroph adenomas

Abstract: The presence of MMs in T2-weighted MRI is a good diagnostic tool to suggest the corticotroph subtype in an apparently nonfunctional pituitary tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 27 publications
(65 reference statements)
4
34
1
Order By: Relevance
“…A recent report proposes that the presence of multiple microcysts on T2‐weighted MRI images distinguishes silent corticotroph macroadenomas from other types of macroadenomas . In the present study, however, although 87·5% of clinically silent corticotroph macroadenomas had multiple microcysts, so did 90% of null cell macroadenomas and 80% of gonadotroph macroadenomas.…”
Section: Discussioncontrasting
confidence: 81%
“…A recent report proposes that the presence of multiple microcysts on T2‐weighted MRI images distinguishes silent corticotroph macroadenomas from other types of macroadenomas . In the present study, however, although 87·5% of clinically silent corticotroph macroadenomas had multiple microcysts, so did 90% of null cell macroadenomas and 80% of gonadotroph macroadenomas.…”
Section: Discussioncontrasting
confidence: 81%
“…Radiologic features are generally similar between SCAs and NFAs [9,10,19,43] though cavernous sinus invasion may be more prevalent in SCAs than in nonfunctioning adenomas [4,20,49,50,63]. One group identified multiple microcysts (<3 mm) of high intensity signal on T2 weighted images in 77% of SCAs compared 21% in CD and 5% of NFAs, and macrocysts in 23% of SCAs [7]. Further, SCAs may have higher rates of intratumoral hemorrhage [9].…”
Section: Clinical Coursementioning
confidence: 99%
“…Langlois et al reported a case series of SCAs (n = 39), and 33% of cases demonstrated >50% fluid content on MRI T2-phase sequences (37). Cazabat et al reported that cystic changes could be found in all SCAs (n = 17), half of corticotroph macroadenomas (n = 14), and only 17% of silent gonadotroph macroadenomas (n = 60) on T2-weighted pituitary MRI sequences in their case series (38). Multiple microcysts were present in most SCAs (13/17, 76.5%), and macrocysts were observed in the remaining four SCAs (4/17, 23.6%).…”
Section: Discussionmentioning
confidence: 95%